Debt Sustainability in the Case of External Debt. An Analysis Based on Italy's Treasury Auctions - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2014)
The objective of this paper is to assess whether external debt makes a difference for public debt stabilization, where external debt is considered through the non-residents' holdings according to a Balance of Payments perspective. The analysis is empirical and considers the case of Italy, one of the world's largest debt issuer. We study the potential effects on the interest rate resulting from the auctions of government bonds to account for the effective cost borne by the Treasury. Our results point towards the irrelevance of the composition of the investor base for debt stabilization.
Keywords: E63; F34; G11; H63; 330; debt stabilization; external debt; primary market; yields; Italy